wound healing activity of Morinda tinctoria Roxb aqueous leaf extract - Rex Jeya Rajkumar, S.; Gnanavel, G.; Muthukumar Nadar, M. S. A.; Sankaranarayanan, Rajkumar (3 Biotech, 2018)
This study investigated the wound healing properties of the aqueous extract of Morinda tinctoria Roxb leaves in rats. The study also provides information on the purification, qualitative, and quantitative analysis of phytochemical components present in M. tinctoria Roxb. Wound contraction and period of epithelialization was determined and topical application of M. tinctoria Roxb aqueous leaf extract showed better healing than orally treated and control groups. The results suggest that the efficacy of M. tinctoria Roxb aqueous leaf extract as a wound healing agent and can also be used as a therapeutic agent for internal as well as external wounds.